Desarrollo de actividades didácticas multimedia complementarias para el software educativo como apoyo didáctico en la área de estudios sociales del nivel de educación general básica enmarcado en los hechos históricos geográficos educativos del cantón Paltas provincia de Loja - Silva Quezada, Olga Maria (2015)
Within this research several problems were found among the following, we lack of educational multimedia activities in the software developed before social studies, we also have insufficient training of teachers in the use of new technological tools; and there is little equipment in schools. In Region 7, province of Loja, canton Paltas socialized educational activities in the three schools "Juny 25" Calvary Hills neighborhood, "December 3" neighborhood Lauro Guerrero and "José María Velasco Ibarra" neighborhood Progress These educational institutions belong to urban parishes Catacocha and Lourdes. The techniques used were the survey via questionnaire of 7 questions to teachers in the area of social studies and diagnostic testing structured 10 questions, based on the contents of the Educational software intended for children of the fourth year of Education General Basic and achieve identify gaps that have, allowing to obtain reliable information. In conclusion of this study it can be said that the development of multimedia activities, will feed on meaningful learning of students; also be of a great use for teachers to use them as teaching materials in social studies classes with regard to historical, geographical and educational facts of Paltas Canton.